ANDROID-BASED CAMPUS GOODS LENDING SYSTEM - Jafar Sidiq, Muhamad; Sukma Indrayana, Andri; Jayusman, Hadi (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
In order to carry out learning activities, students need supporting tools such as laptops and others, with the aim of facilitating these learning activities. On the other hand, the campus provides the necessary facilities and tools, and can be borrowed with the provisions of the applicable regulations, so the activity of borrowing goods often occurs between students and the campus. In the ongoing lending system, many problems are found because everything is still completely manual, which results in frequent data loss, and misunderstandings. To overcome this, the author creates a system that will facilitate the activity of borrowing goods to be more efficient, by creating an android-based application that can store data into the database so that the data is stored safely.